Determinants of Financial Performance of Islamic Banking in Malaysia - Nur Amirah, Ismail; Nurul Syuhada, Zaidi; Ahmad Syubaili, Mohamed; Mohd Naim, Kamaruzaman (Human Resource Management Academic Research Society (HRMARS), 2018)
This research was conducted to investigate the determinants of the financial performance of Islamic banking in Malaysia. The performance of Islamic Bank measured based on return on asset (ROA), while the independent variables examined were capital adequacy (CA), asset quality (AQ), and liquidity management (LM). The data for this research were collected from twelve out of sixteen Islamic Banks in Malaysia listed by Bank Negara Malaysia. The annual reports were analyzed for six years which were from the year 2010 until 2016. The findings revealed that there is a significant relationship between asset quality and liquidity management towards the performance of Islamic Banking in Malaysia. However, there is insignificant relationship between capital adequacies towards the performance of Islamic Banking in Malaysia. Nevertheless, there are still other factors that may affect the performance of Islamic Banking in Malaysia.